2017
DOI: 10.1002/eap.1485
|View full text |Cite
|
Sign up to set email alerts
|

Movements of a deep‐water fish: establishing marine fisheries management boundaries in coastal Arctic waters

Abstract: Management boundaries that define populations or stocks of fish form the basis of fisheries planning. In the Arctic, decreasing sea ice extent is driving increasing fisheries development, highlighting the need for ecological data to inform management. In Cumberland Sound, southwest Baffin Island, an indigenous community fishery was established in 1987 targeting Greenland halibut (Reinhardtius hippoglossoides) through the ice. Following its development, the Cumberland Sound Management Boundary (CSMB) was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…Moreover, there is a large data gap on movement behaviour of marine fishes compared to marine mammals and seabirds in the Arctic. Ongoing studies by The Ocean Tracking Network have provided insight into the movement ecology of key pelagic and deep‐water fishes (Hussey et al., ; Kessel et al., ; Moore et al., ) with implications for fisheries and conservation management (Barkley et al., ; Hussey et al., ). Continued telemetry studies on Arctic fishes along with other marine predators will further expand our knowledge of the mechanisms and processes that affect Arctic ecosystem structure and function and will improve our understanding of important areas for conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a large data gap on movement behaviour of marine fishes compared to marine mammals and seabirds in the Arctic. Ongoing studies by The Ocean Tracking Network have provided insight into the movement ecology of key pelagic and deep‐water fishes (Hussey et al., ; Kessel et al., ; Moore et al., ) with implications for fisheries and conservation management (Barkley et al., ; Hussey et al., ). Continued telemetry studies on Arctic fishes along with other marine predators will further expand our knowledge of the mechanisms and processes that affect Arctic ecosystem structure and function and will improve our understanding of important areas for conservation.…”
Section: Discussionmentioning
confidence: 99%
“…migration routes, spatio-temporal habitat use and movement behaviour of key species) in these environments has significantly improved in recent years. This knowledge provides a scientific basis for fisheries management (Hussey et al, 2017), species conservation, marine spatial planning (Abecasis et al, 2014;Afonso et al, 2016) and environmental impact assessment (Winter et al, 2010;Reubens et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, Greenland halibut were tagged within the 22 km zone prioritized for the development of small‐scale community fisheries. The majority of these tagged fish did not exhibit the level of residency previously reported in fjord habitats (Boje, ; Boje et al., ; Hussey et al., ), but were instead highly migratory, using the coastal area in the late summer months then exiting into the offshore as ice formed. Variability in movement measures was observed among individuals while in coastal waters as a result of differing movement rates and residency times within sections of the coastal environment.…”
Section: Discussionmentioning
confidence: 81%
“…In the Canadian Arctic, mark–recapture work in Cumberland Sound revealed that fish tagged in the northern end of the Sound were also resident, while fish tagged at the entrance were found to migrate to both inshore and offshore areas (Treble, ). More recently, acoustic telemetry found that fish in Cumberland Sound moved from north to south on a seasonal basis (Hussey et al., ), undertaking movements similar to fish in Disko Bay (Boje et al., ), but with some evidence for emigration. While most studies on Greenland halibut have suggested high levels of residency within coastal deep water fjords, this study suggests that transient movements can occur during the summer–fall period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation